Klug technology: desenvolvimento de produtos inovadores em uma startup brasileira - Garbe, Hugo (2023)
The present study has the general objective of analyzing the development and launch of three high-tech products in the startup Klug Technology, from the perspective of innovation. And, as specific objectives, to identify the innovation process used for the development and launch of new Klug Technology products; in addition to its main obstacles and facilitators. In theoretical terms, the main trends of innovation were used as a background, specifically in light of the technology products developed in the startup Klug Technology, which is the company founded by the author of this work. The Methodology section addresses four different topics. In the first one, a presentation is made about Klug Technology and its foundation; in the second topic, Klug's main products are presented, their market relevance and their characteristics; in the third topic addressed, the theory of the single case study is discussed, which is the research methodology of this thesis. Interviews were carried out with the 4 partners of Klug techonology in order to investigate the main points of view regarding the innovation process used for the development and launch of new products in the company. The present work found that the main facilitators in the development process of Klug technology products are from the idea to the virtual prototyping process. The main obstacles found in the development of Klug technology products are, essentially when it comes to technology and innovation, experimentation has to take into account several details, such as: user journey, production cost, and the adjustments demanded by the Marketplace. The credit and financial limitation is also a point verified in the analysis, which can impact the development of high technology products, since the investments demand large investments, and it is not necessarily possible to have a quick return, or, many times, it is not known whether there will be return.